Chemo-Enzymatic Synthesis of Enantiopure β-Antagonist (S)-Betaxolol - Susanne Hansen Troøyen; Elisabeth Egholm Jacobsen (Catalysts, 2022)
The β-blocker (S)-betaxolol has been synthesized in 99% enantiomeric excess (ee) from the commercially available precursor 4-(2-hydroxyethyl)phenol. The racemic chlorohydrin 1-chloro-3-(4-(2-(cyclopropylmethoxy)ethyl)phenoxy)propan-2-ol was esterified with vinyl acetate catalyzed by lipase B from Candida antarctica, which gave the R-chlorhydrin (R)-1-chloro-3-(4-(2-(cyclopropylmethoxy)ethyl)phenoxy)propan-2-ol in 99% ee with 38% yield. The enantiomeric excess of the R-chlorohydrin was retained in an amination reaction with isopropylamine in methanol to yield (S)-betaxolol in 99% ee and with 9% overall yield. We are under way to improve the yield.